An Evaluation of The Theory of Abuse of Rights: Between Sharia and Civil Law a Comparative and Analytical Study - Rashed, Tarek; Saad, Mahmoud; Yahia, Khawlah A. (International Journal of Membrane Science and Technology, 2023)
Purpose: This research aims to show how Egyptian and Qatari legislators codify the “abuse of rights” theory and compare it with Islamic law. This is done to correct the defects and deficiencies in the Egyptian and Qatari legal texts. Although the Arab laws are considered among the first laws that adopted this theory, they did not establish private regulation for this theory in their legal rules. Instead, they copied French civil law, which created a conflict between Islamic jurisprudential rules and the legal texts. Methodology: This Article has been written using two methodologies to find answers to the fundamental questions raised by this Article. The first methodology analyzes the legal texts that regulate the theory of Abuse of Rights in Egyptian and Qatari laws. In contrast, the second one is based on comparing the legal texts with Islamic jurisprudential rules. Findings: In the end, we concluded that the theory of “abuse of rights” was stipulated in the Egyptian and Qatari Civil Codes, and judicial rulings established the application of this theory. However, Article (5) of the Egyptian Civil Code and Article (63) of the Qatari Civil Code do not involve this theory. On the other hand, the general texts in Mecelle have organized this theory better and more accurately. Originality: The originality of this Article lies in the fact that it analyzed the position of the Egyptian and Qatari legal texts and commented on the judicial provisions issued by the Egyptian and Qatari courts of Cassation and the Arab courts, and the opinions of civil law jurists related to “abuse of the right.” Moreover, it criticized these texts and highlighted aspects of their deficiencies in comparison with the jurisprudential rules extracted from Islamic law.